RKIP mediates autoimmune inflammation by positively regulating IL‐17R signaling. (19th April 2018) - Lin, Wenlong; Wang, Ning; Zhou, Kangxing; Su, Fasheng; Jiang, Yu; Shou, Jianan; Liu, Huan; Ma, Chunmei; Qian, Youchun; Wang, Kai; Wang, Xiaojian
Abstract: Th17 cells contribute to the development of autoimmune diseases by secreting interleukin‐17 (IL‐17), which activates its receptor (IL‐17R) that is expressed on epithelial cells, macrophages, microglia, and resident neuroectodermal cells. However, the mechanisms through which IL‐17R‐mediated signaling contributes to the development of autoimmune disease have not been completely elucidated. Here, we demonstrate that Raf‐1 kinase inhibitor protein (RKIP) deficiency in mice ameliorates the symptoms of experimental autoimmune encephalomyelitis (EAE). Adoptive T‐cell‐transfer experiments demonstrate that RKIP plays a predominant role in Th17‐mediated, but not in Th1‐mediated immune responses. RKIP deficiency has no effect on Th17‐cell differentiation ex vivo, nor does it affect Th17‐cell differentiation in EAE mice. However, RKIP significantly promotes IL‐17R‐induced proinflammatory cytokine and chemokine production. Mechanistically, RKIP directly interacts with IL‐17RA and Act1 to promote the formation of an IL‐17R‐Act1 complex, resulting in enhanced MAPK‐ and P65‐mediated NF‐κB activation and downstream cytokine production. Together, these findings indicate that RKIP functions as an essential modulator of the IL‐17R‐Act1 axis in IL‐17R signaling, which promotes IL‐17‐induced inflammation and autoimmune neuroinflammation. Synopsis: The Raf‐1 kinase inhibitor protein participates in the pathogenesis of IL‐17‐mediated autoimmune diseases and inflammation by promoting the formation of the IL‐17RA‐Act1 complex, required for downstream signaling and cytokine production. RIPK promotes EAE pathogenesis via enhanced IL‐17R‐mediated signaling and inflammation. RKIP positively regulates IL‐17‐induced inflammation in vitro and in vivo . RKIP interacts with IL‐17R and Act1, thereby stabilizing the IL‐17R‐Act1 complex. Abstract : The Raf‐1 kinase inhibitor protein participates in the pathogenesis of IL‐17‐mediated autoimmune diseases and inflammation by promoting the formation of the IL‐17RA‐Act1 complex, required for downstream signaling and cytokine production.